Proceso de atención de enfermería aplicado en neonato con síndrome de dificultad respiratoria. - Muñoz Diaz, Joselyn Viviana (2022)
Respiratory distress syndrome, also called hyaline membrane disease, is the most common pathology in the Neonatal Intensive Care Unit, it occurs in preterm newborns and is the main cause of morbidity and mortality of respiratory origin. Its incidence is reported in 5 to 10% of newborns and this increases significantly at a lower gestational age, with a higher incidence in patients weighing less than 1,200 g and 30 weeks of gestation, this disease is caused by a lack of pulmonary surfactant, a substance that Its main function is to reduce the surface tension forces of the alveoli and maintain the stability and volume of the lungs during expiration. Due to the deficiency of surfactant there is a tendency to alveolar collapse; this produces progressive atelectasis, intrapulmonary circulatory shunt, and hypoxemia. Clinically, it is characterized by progressive early-onset respiratory distress, from birth or in the first 6 hours of life. This respiratory distress is manifested by generally audible grunting, nasal flaring, xiphoid retraction, polypnea, and rapidly increasing FiO2 (fraction of inspired oxygen) requirements. The vesicular murmur is usually diminished, as well as the anteroposterior diameter of the thorax; in severe cases, there is thoracoabdominal dissociation. Edema is often present, and diuresis is decreased. There are factors that increase the risk of presenting this disease: prematurity (more frequently at a lower gestational age), cesarean section without labor, history of respiratory distress syndrome in previous children, maternal hemorrhage prior to delivery, perinatal asphyxia, child of a mother diabetic, erythroblastosis fetalis. Among the appropriate treatments used for respiratory distress syndrome are continuous positive pressure, mechanical ventilation and the use of exogenous surfactant, which vary the course of the disease and have a significant impact on morbidity and mortality. The presence of surfactant in amniotic fluid is related to the degree of fetal lung maturity. Chest radiography is essential in the diagnosis; the characteristic radiological image shows increased homogeneous lung density. Blood gas determination shows oxygen requirements that rapidly necessitate inspired fraction of oxygen above 30-40%. Depending on the severity of the case, there may be respiratory and/or metabolic acidosis. The clinical and radiological picture can be identical: it helps to differentiate the perinatal history and the rapidly progressive evolution and with a greater tendency to cardiovascular compromise in the case of pneumonia. In the first hours after birth, transient neonatal tachypnea must also be differentiated, in which the course is more favorable and the patient has adequate lung volume. Current therapy focuses on the main preventive measures such as good prenatal control. In case of threat of premature birth, measures should be taken to prolong the pregnancy, the appropriate use of medications that inhibit labor, the use of steroids in the pregnant mother to produce lung maturation. All of these measures help decrease the incidence of RDS. During her hospitalization, the care applied to pregnant women is aimed at improving survival, as well as reducing the risk of premature birth and its morbidity.